ANALISIS YURIDIS TERHADAP KEPUTUSAN HAKIM TENTANG TINDAK PIDANA MENGHILANGKAN NYAWA DI PENGADILAN NEGERI KOTA LUBUKLINGGAU KELAS IA (STUDI KASUS PUTUSAN NOMOR :301/ PID.B/2020/PN-LLG) - Anggraini, Devi; Amanda, Olga; Fitriyani, Fitriyani; Fuadi, Ahmad (Law Journal (LAJOUR), 2025)
This journal analyzes the judge’s decision in a criminal case of taking another person’s life at the Lubuklinggau District Court, Class 1A, through a case study of Decision Number 301/PID.B/2020/PN-LLG. The study aims to understand the application of the elements in Articles 338 and 340 of the Indonesian Criminal Code (KUHP) and the judge’s considerations in delivering the verdict. The research employs a normative-empirical legal method, using a conceptual and statutory approach. Data were collected through interviews and literature studies. The findings indicate that the elements in Article 338 of the Criminal Code include “whoever,” “intentionally,” and “takes another person’s life,” while Article 340 emphasizes the element of “premeditation,” which must be proven by showing a time lapse that allows the perpetrator to reconsider their intention. In this case, the judge based the decision on evidence, legal facts, and the application of Article 338 KUHP, resulting in a sentence aligned with intentional killing without proven premeditation.